Analisa dan Perancangan Kios Informasi Taman Buah Mekarsari Berbasis Multimedia - Rudi Sutomo (Teknik Informatika, 2018)
Tourism objects is one of the highest commodity in Indonesia. By the various potential landmarks and cultures, Indonesia has huge opportunity to raise the GDP from this sector. One of the crucial issue on maintaining tourism object is on the credible and accessible information supply. People may not be coming since do not have any idea about a certain tourism object. It is the case on Taman Buah Mekarsari. Intended to attract thevisitor by supplying the information about taman buah Mekarsari, a Multimedia-based informations system, Kios Informasi Taman Buah Mekarsari, is developed. The proposed digitalized information system will provide the credible informations about Taman Buah Mekarsari and all its interesting attraction. Besides, it offers the ease of accessibility for the users.